Analisis Persepsi Konsumen Terhadap Digital Marketing Produk Abon Ikan Lele Berbasis Social Media di Kabupaten PasuruanDigital Marketing is a marketing activity or promotion of a product and brand that is carried out using digital media or the internet, - Musta’in; Ernawati (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2022)
Digital Marketing is a marketing activity or promotion of a product and brand that is carried out using digital media or the internet, either by using websites, e-commerce, social media, email, adwords and blogs. This study aims to identify consumer behavior and measure consumer perceptions of digital marketing or online promotion of catfish floss products based on social media in the Pasuruan Regency area. This research method uses descriptive qualitative method, Important Performance Analysis and Customer Satisfaction Index. The measurement of consumer perception uses a Likert scale with 4 scales starting from strongly disagree (scale 1), disagree (scale 2), agree (scale 3) to strongly agree (scale 4). The number of respondents who were used as samples was 100 people. Consumer behavior in digital marketing of shredded catfish fishery products with the result that consumers buy shredded catfish fishery products through digital marketing for practical reasons (33%), sources of purchasing information from social media (42%), consumers pay attention to quality levels (45%), consumers buy an average of <1kg of fishery products (57%) and consumers make repurchases (79%). Consumer perceptions of the overall attributes of digital marketing of fishery products are satisfied (65%), with the main priority of improving performance lies in the price and quality attributes of fishery products from digital marketing